2021
DOI: 10.1002/ab.22002
|View full text |Cite
|
Sign up to set email alerts
|

Linking violent video games to cyberaggression among college students: A cross‐sectional study

Abstract: To explore the relationship between exposure to violent video games and college students' cyberaggressive behavior and its internal mechanism, a cross‐sectional survey was carried out with a sample of 1141 college students who completed the Violent Video Game Listing Questionnaire (VVLQ), Adolescent Online Aggressive Behavior Scale (AOABS), Beliefs Supportive of Violence Scale (BSVS), and Trait Anger Scale (TAS). The results showed that (1) exposure to violent video games was positively associated with college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
2
0
2
Order By: Relevance
“…Previous studies have demonstrated the validity and reliability of this self-report measure of violent game exposure [ 54 ]. This method of measuring has been extensively employed in earlier studies, including those conducted in China [ 5 , 55 , 56 ]. In accordance with the study, we added a measure of exposure to competitive video games in reference to the measure of violent game exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated the validity and reliability of this self-report measure of violent game exposure [ 54 ]. This method of measuring has been extensively employed in earlier studies, including those conducted in China [ 5 , 55 , 56 ]. In accordance with the study, we added a measure of exposure to competitive video games in reference to the measure of violent game exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Όσον αφορά το γεγονός ότι η έμμεση επιθετικότητα δεν μεταβλήθηκε σημαντικά, είναι δυνατόν να υποστηριχθεί ότι το συγκεκριμένο είδος επιθετικότητας σχετίζεται κυρίως με τη συντελεστική επιθετικότητα, δηλαδή προσχεδιασμένες επιθετικές ενέργειες, σε αντίθεση με τη σωματική και τη λεκτική επιθετικότητα, που συνδέονται κυρίως με την αντιδραστική επιθετικότητα, δηλαδή τις άμεσες επιθετικές ενέργειες λόγω ματαίωσης ή διέγερσης (Wrangham, 2017) και ως εκ τούτου, η πειραματική διαδικασία δεν αρκούσε για να επιδράσει στη συγκεκριμένη διάσταση της επιθετικότητας. Ωστόσο, σύμφωνα με πρόσφατη έρευνα σε φοιτητικό πληθυσμό (Li, 2022) διαπιστώθηκε ότι η ενασχόληση με βίαια ηλεκτρονικά παιχνίδια συνδέθηκε με υψηλότερα ποσοστά διαδικτυακού εκφοβισμού, ο οποίος συνιστά μορφή έμμεσης επιθετικότητας. Επομένως, ενδέχεται τα βίαια ηλεκτρονικά παιχνίδια να προκαλούν αύξηση και της έμμεσης επιθετικότητας αλλά μόνο στα εικονικά, διαδικτυακά περιβάλλοντα και όχι στην πραγματική ζωή.…”
Section: αποτελέσματα ανάλυσης παλινδρόμησηςunclassified
“…Σε πειραματική μελέτη (Unsworth et al, 2007), η έκθεση των συμμετεχόντων σε βίαιο ηλεκτρονικό παιχνίδι έδειξε, αναφορικά με τα επίπεδα θυμού, σε άλλους συμμετέχοντες αύξηση και σε άλλους μείωση, αλλά στην πλειοψηφία των συμμετεχόντων δεν βρέθηκε καμία μεταβολή. Επίσης, σε πρόσφατη μελέτη (Li, 2022) διαπιστώθηκε ότι ο θυμός που σχετίζεται με την κατάσταση αυξήθηκε μετά την ενασχόληση με τα βίαια ηλεκτρονικά παιχνίδια, ενώ ο θυμός ως χαρακτηριστικό της προσωπικότητας των συμμετεχόντων συνδεόταν με υψηλή παρορμητικότητα και περισσότερες ώρες ενασχόλησης με τα συγκεκριμένα παιχνίδια. Ωστόσο, οι σχετικές μελέτες σπανίζουν και το θέμα χρήζει περαιτέρω διερεύνησης, προκειμένου να κατανοηθεί ευκρινέστερα η σημασία σχεδιασμού και εφαρμογής παρεμβάσεων διαχείρισης και μείωσης του θυμού (Anderson & Carnagey, 2009˙ Morrison et al, 2021.…”
unclassified
“…According to social learning theory (Bandura et al, 1961, Gentile & Gentile, 2008, players may begin to internalize and replicate behaviors and identities modeled within the game, often characterized by a heightened propensity for aggression (Haninger & Thompson, 2004;KFF, 2002;Thompson & Haninger, 2001). As a result, long-term exposure to VVGs is associated to an increased accessibility to aggressive responses (e.g., Gentile et al, 2014), moral disengagement with aggressive acts (e.g., Teng et al, 2017) and an increased acceptance of violence (e.g., Li, 2022). Essentially, prolonged exposure to VVGs not only increases the probability of players considering aggressive options in conflict situations but also reduces moral inhibitions against such actions and normalizes these responses as appropriate, thereby culminating in an increased tendency towards aggression.…”
Section: Introductionmentioning
confidence: 99%